Exploring the Leaves of Annona muricata L. as a Source of Potential Anti-inflammatory and Anticancer Agents - Abdul Wahab, Siti Mariam; Jantan, Ibrahim; Haque, Md. Areeful; Arshad, Laiba (Frontiers in Pharmacology, 2018)
The use of anti-inflammatory natural products to treat inflammatory disorders for cancer prevention and therapy is an appealing area of interest in the last decades. Annona muricata L. is one of the many plant extracts that have been explored owing to their anti-inflammatory and anticancer effects. Different parts of A. muricata especially the leaves have been used for various ethnomedicinal purposes by traditional healers to treat several diseases including cancer, inflammation, diabetes, liver diseases, and abscesses. Some of these experience-based claims on the use of the plant have been transformed into evidence-based information by scientific investigations. The leaves of the plant have been extensively investigated for its diverse pharmacological aspects and found eminent for anti-inflammatory and anticancer properties. However, most studies were not on the bioactive isolates which were responsible for the activities but were based on crude extracts of the plant. In this comprehensive review, all significant findings from previous investigations till date on the leaves of A. muricata, specifically on their anti-inflammatory and anticancer activities have been compiled. The toxicology of the plant which has been shown to be due to the presence of neurotoxic annonaceous acetogenins and benzyltetrahydro-isoquinoline alkaloids has also been updated to provide recent information on its safety aspects. The present knowledge of the plant has been critically assessed, aimed at providing direction towards improving its prospect as a source of potential anti-inflammatory and anticancer agents. The analysis will provide a new path for ensuring research on this plant to discover new agents to treat inflammatory diseases and cancer. Further in vitro and in vivo studies should be carried out to explore the molecular mechanisms underlying their anti-inflammatory responses in relation to anticancer activity and more detail toxicity study to ensure they are safe for human consumption. Sufficient preclinical data and safety data generated will allow clinical trials to be pursued on this plant and its bioactive compounds.